Complete arsenic-based respiratory cycle in the marine microbial communities of pelagic oxygen-deficient zones - Saunders, Jaclyn K. (Proc Natl Acad Sci U S A, 2019)
Microbial capacity to metabolize arsenic is ancient, arising in response to its pervasive presence in the environment, which was largely in the form of As(III) in the early anoxic ocean. Many biological arsenic transformations are aimed at mitigating toxicity; however, some microorganisms can respire compounds of this redox-sensitive element to reap energetic gains. In several modern anoxic marine systems concentrations of As(V) are higher relative to As(III) than what would be expected from the thermodynamic equilibrium, but the mechanism for this discrepancy has remained unknown. Here we present evidence of a complete respiratory arsenic cycle, consisting of dissimilatory As(V) reduction and chemoautotrophic As(III) oxidation, in the pelagic ocean. We identified the presence of genes encoding both subunits of the respiratory arsenite oxidase AioA and the dissimilatory arsenate reductase ArrA in the Eastern Tropical North Pacific (ETNP) oxygen-deficient zone (ODZ). The presence of the dissimilatory arsenate reductase gene arrA was enriched on large particles (>30 um), similar to the forward bacterial dsrA gene of sulfate-reducing bacteria, which is involved in the cryptic cycling of sulfur in ODZs. Arsenic respiratory genes were expressed in metatranscriptomic libraries from the ETNP and the Eastern Tropical South Pacific (ETSP) ODZ, indicating arsenotrophy is a metabolic pathway actively utilized in anoxic marine water columns. Together these results suggest arsenic-based metabolisms support organic matter production and impact nitrogen biogeochemical cycling in modern oceans. In early anoxic oceans, especially during periods of high marine arsenic concentrations, they may have played a much larger role.